2018
DOI: 10.1103/physrevb.97.144423
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetism and phase transitions in noncentrosymmetric UIrSi3

Abstract: Magnetization and specific heat measurements on a UIrSi 3 single crystal reveal Ising-like antiferromagnetism below T N = 41.7 K with easy magnetization direction along the c-axis of tetragonal structure. The antiferromagentic ordering is suppressed by magnetic fields > H c (µ 0 H c = 7.3 T at 2 K) applied along the c-axis. The first-order metamagnetic transition at H c exhibits asymmetric hysteresis reflecting a slow reentry of the complex ground-state antiferromagnetic structure with decreasing field. The hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 40 publications
(48 reference statements)
9
26
0
Order By: Relevance
“…The magnetization as a function of field behavior at 6 K is complex and exhibits a second magnetic hysteresis loop at high fields (above 3000 kA/m), see Figure 9b). A similar behavior to the data presented in Figure 9b has been observed in single crystals of the antiferromagnet UIrSi3, which crystallizes in the tetragonal BaNiSn3 structure type [33]. The magnetic moments in UIrSi3 order ferromagnetically in the ab plane with the moments aligned along the c axis.…”
Section: H-induced Magnetic Property Changessupporting
confidence: 83%
“…The magnetization as a function of field behavior at 6 K is complex and exhibits a second magnetic hysteresis loop at high fields (above 3000 kA/m), see Figure 9b). A similar behavior to the data presented in Figure 9b has been observed in single crystals of the antiferromagnet UIrSi3, which crystallizes in the tetragonal BaNiSn3 structure type [33]. The magnetic moments in UIrSi3 order ferromagnetically in the ab plane with the moments aligned along the c axis.…”
Section: H-induced Magnetic Property Changessupporting
confidence: 83%
“…Experimental studies concerning tricriticality in antiferromagnets are quite rarely reported in literature although understanding of these phenomena has fundamental importance. TCPs have been reported in several uranium antiferromagnets exhibiting Ising-like behavior caused by very strong magnetocrystalline anisotropy [23][24][25][26][27] . We mark the tentatively considered TCP in the magnetic phase diagram in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In previously studied AFM materials [41][42][43], the disappearance of the hysteresis has been considered as one of the signatures of a tricritical point (TCP) in the phase diagram which separates first-and second-order AFM transitions and exhibiting Ising-type anisotropy [42,[44][45][46][47]. This supports the existence of TCP in U2Rh2Pb around Ttc = 13 K and µ0Htc = 4 T. It should be pointed out that TCP is an inherent feature of a broad class of antiferromagnets, in which the metamagnetic transition at low temperatures is of the first-order type and magnetic critical point in zero field is of the second-order type, and hence does now imply any temperature variations of magnetic interactions [48].…”
Section: Magnetic Phase Diagrammentioning
confidence: 99%